Theatre of the new political. Performance of law by Michał Zadara (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The chapter analyzes the process of emerging and defining the political in Polishtheatre of the last years. By discussing the most essential views on this matter,performed by theatre scholars (Paweł Mościcki, Bartosz Frąckowiak, TomaszPlata) and theorists of critical art (Jacques Rancière, Nicolas Bourriaud, ChantalMouffe, Alain Badiou), the author tries to review previous observations and toarrange them into a common conceptual grid. In refer to such organized frameworkthe new form of the political in Polish theatre – performances of law by MichałZadara are investigated: Sprawiedliwość (Justice) (2018) and Odpowiedzialność(Responsibility) (2022). These two case studies provides an original breakagainst to the traditional theatrical frame by inviting scholars and lawyers to thecreative process and by redefining Brechtian V-effect in a conspicuous break withfiction in order to expand an efficiency of art: by actual legal activity – preparingreal lawsuits, and by creating direct relation with the audience.